2019
DOI: 10.1111/apha.13345
|View full text |Cite
|
Sign up to set email alerts
|

Blunted leptin sensitivity during hedonic overeating can be reinstated by activating galanin 2 receptors (Gal2R) in the lateral hypothalamus

Abstract: Aim Since foods with high hedonic value are often consumed in excess of energetic needs, this study was designed to identify the mechanisms that may counter anorexigenic signalling in the presence of hedonic foods in lean animals. Methods Mice, in different states of satiety (fed/fasted, or fed/fasted and treated with ghrelin or leptin, respectively), were allowed to choose between high‐fat/high‐sucrose and standard foods. Intake of each food type and the activity of hypothalamic neuropetidergic neurons that r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 78 publications
(166 reference statements)
1
14
0
Order By: Relevance
“…7,15 Activation of galanin receptor subtype 2 in the lateral hypothalamus reinstated blunted leptin sensitivity during hedonic overeating of palatable foods in lean animals. 24 The results in the present study showed that administration of both hormones compromised their effects on food intake and bodyweight. The combined roles of both hormones were lower than galanin, but higher than leptin.…”
Section: Discussionsupporting
confidence: 45%
“…7,15 Activation of galanin receptor subtype 2 in the lateral hypothalamus reinstated blunted leptin sensitivity during hedonic overeating of palatable foods in lean animals. 24 The results in the present study showed that administration of both hormones compromised their effects on food intake and bodyweight. The combined roles of both hormones were lower than galanin, but higher than leptin.…”
Section: Discussionsupporting
confidence: 45%
“…In addition to metabolic needs, the hedonic effects of food can also induce food intake in individuals, which may be because eating food can make them feel better and relieve stress [57]. Studies have demonstrated that leptin and ghrelin are responsible for both homeostatic and hedonic aspects of feeding by regulating dopamine signaling [57][58][59][60]. Overall, these results show that the gut microbiota may regulate feed intake by regulating leptinrelated signaling pathways.…”
Section: Ghrelinmentioning
confidence: 91%
“…The food preference test was performed with minor modifications as described earlier in Leidmaa et al [ 34 ]. All the mice were housed in single cages and, on days 1–3, mice received regular food.…”
Section: Methodsmentioning
confidence: 99%